2016
DOI: 10.1016/j.jallcom.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of micro-mechanisms in hydrogen induced cracking in nickel-based superalloy 718

Abstract: Superalloys are widely used in a variety of applications including aerospace and land based gas turbine engines and nuclear power plants. The aerospace industry has experienced hydrogen embrittlement problems for many years. Hydrogen embrittlement is a delayed failure mechanism related to loss of ductility due to the presence of hydrogen in the material. Hydrogen embrittlement of the nickel-iron based superalloy 718 has been investigated using slow strain rate tests for pre-charged material and also in-situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(25 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…Among all the proposed HE mechanisms, it seems the H-enhanced decohesion (HEDE) mechanism to be the most relevant one when the GBs are involved. The intergranular failure by H is explained in terms of reduction of the cohesive strength of GB by first-principles studies [24][25][26][27] and is shown experimentally on different materials [23,[28][29][30][31][32]. However, the work done by McMahon [33] showed that H-induced intergranular brittleness is strongly depended on the amount of impurities segregated to the GB.…”
Section: (C) Grain Boundarymentioning
confidence: 99%
“…Among all the proposed HE mechanisms, it seems the H-enhanced decohesion (HEDE) mechanism to be the most relevant one when the GBs are involved. The intergranular failure by H is explained in terms of reduction of the cohesive strength of GB by first-principles studies [24][25][26][27] and is shown experimentally on different materials [23,[28][29][30][31][32]. However, the work done by McMahon [33] showed that H-induced intergranular brittleness is strongly depended on the amount of impurities segregated to the GB.…”
Section: (C) Grain Boundarymentioning
confidence: 99%
“…Several EBSD runs were carried out at various locations within the joint, namely, along the dissimilar weld joint root, above the weld root, within the In718 HAZ and base metal and within the PP-Ni HAZ and base metal. A step size of 0.2 µm and 4 µm was used in the EBSD analyses and more detailed information about post processing of the EBSD results and applying these data in multiscale modelling can be found elsewhere [19,20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Panda put forward a hybrid optimization technique namely Neuro-Grey Modeling which carries out the parameter design and optimization of multi-machining characteristics of WEDM process and concluded that the model was reliable and can be implemented fast when compared with genetic algorithm [32]. It has been reported that the localized microstructural parameters such as phase distribution, grain size, distribution & grain structure also plays an important role on the effect of process parameters [35][36][37][38][39][40][41][42]. It also has been reported that the machine learning based ANN model has been used to predict the mechanical properties of metals & alloys [33,34,43].…”
Section: Introductionmentioning
confidence: 99%